Constructing Simple Sentences: Effects of a Writing Fluency Intervention for Middle School Students With Disabilities. (April 2021) - Panos, Kristin L.; Datchuk, Shawn M.
Simple sentence construction is a foundational writing skill that forms the building blocks of advanced writing. Many middle school students with disabilities struggle to consistently construct simple sentences, thereby hindering development of written expression. The present study used a single-case, multiple-baseline across participants design to investigate the effects of a multicomponent intervention on fluency of sentence construction in response to picture-word prompts. During intervention, three middle school students with disabilities completed six explicit instruction lessons, followed by 15 sessions of timed practice, referred to as sentence instruction and frequency building to a performance criterion. After the first few sentence instruction lessons, all students gradually increased the accuracy and frequency of word sequences during intervention. Tau- U values for writing sequences were large. After completing intervention, all students maintained levels similar to intervention. Results are discussed in the context of writing fluency, prior intervention studies, and implications for practice.